One-Step Generation and Purification of Cell-Encapsulated Hydrogel Microsphere With an Easily Assembled Microfluidic Device - Zhang, Tao; Zhang, Hong; Zhou, Wuping; Jiang, Keming; Liu, Cong; Wang, Ru; Zhou, Yuanshuai; Zhang, Zhiqiang; Mei, Qian; Dong, Wen-Fei; Sun, Minxuan; Li, Haiwen (Frontiers in Bioengineering and Biotechnology, 2022)
Cell-laden hydrogel microspheres with uniform size show great potential for tissue repair and drug screening applications. Droplet microfluidic systems have been widely used for the generation of cell-laden hydrogel microspheres. However, existing droplet microfluidic systems are mostly based on complex chips and are not compatible with well culture plates. Moreover, microspheres produced by droplet microfluidics need demulsification and purification from oil, which requires time and effort and may compromise cell viability. Herein, we present a simple one-step approach for producing and purifying hydrogel microspheres with an easily assembled microfluidic device. Droplets were generated and solidified in the device tubing. The obtained hydrogel microspheres were then transferred to a tissue culture plate filled with cell culture media and demulsified through evaporation of the oil at 37°C. The removal of oil caused the gelled microspheres to be released into the cell culture media. The encapsulated cells demonstrated good viability and grew into tumor spheroids in 12–14 days. Single cell-laden hydrogel microspheres were also obtained and grown into spheroid in 14 days. This one-step microsphere generation method shows good potential for applications in automated spheroid and organoid cultures as well as drug screening, and could potentially offer benefits for translation of cell/microgel technologies.